PENGARUH KEPUASAN KONSUMEN DALAM MEMEDIASI HUBUNGAN KUALITAS PRODUK DAN E-WOM TERHADAP LOYALITAS PELANGGAN (Studi Pengguna Tiktok Shop di Fakultas Ekonomi Dan Bisnis di Universitas Abdurachman Saleh Situbondo 2022-2023) - Faiza, Nur; Wahyuni, Alfi; Azizah, Rofiatul; Citra, Yulia; Firdaus, Dimas Alif; Fauzi, Andrian Anang (Growth, 2024)
Customer loyalty is a crucial variable in sustainable business strategies. A company’s success depends not only on acquiring new customers but also on its ability to maintain long-term relationships with existing customers. Therefore, it is important to understand the factors that can build and enhance customer loyalty. This study aims to examine whether product quality has a positive effect on satisfaction, whether e-WOM has a positive effect on satisfaction, whether product quality has a positive effect on loyalty, whether e-WOM has a positive effect on loyalty, and whether satisfaction has a positive effect on loyalty. Additionally, this study investigates the role of satisfaction in mediating the relationship between product quality and e-WOM towards customer loyalty. The population involves all students from the Faculty of Economics, Abdurachman Saleh University Situbondo, who are TikTok Shop users, with a sample size of 180 respondents. Data were collected using Google Forms and analyzed using SmartPLS. The analysis results show that product quality positively influences satisfaction, e-WOM positively influences satisfaction, product quality positively influences loyalty, e-WOM positively influences loyalty, satisfaction positively influences loyalty, and satisfaction mediates the relationship between product quality and e-WOM towards customer loyalty.